Design and performance evaluation of a novel broadband THz modulator based on graphene metamaterial for emerging applications - Tiang, Jun Jiat; Soliman, Naglaa F.; Khan, Imran; Choi, Jaeyoung; Chung, Hee Chan; Madsen, Dag Øivind (Frontiers in Materials, 2023)
Metamaterials consist of periodic arrangements of artificial subwavelength units that possess electromagnetic properties not present in natural media. It has attracted more interest due to its ability to alter electromagnetic radiation in a flexible manner, which has resulted in the development of multiple radio frequency devices based on metamaterials. Metamaterials with the required frequency band for electric or magnetic resonance can be made using unit cell structure. The incident electromagnetic wave will enter the metamaterials and be kept there in the absence of reflection. This paper proposes a novel broadband THz absorber filter based on graphene for emerging applications. The proposed structure comprised of three parts. The top layer consists of graphene, the middle layer consists of dielectric and the bottom layer is made up of gold. The proposed structure is experimentally designed and validated using the COMSOL simulator. Simulation results show that the proposed absorber has better performance as compared with existing methods.